On some integral equations with the generalized Legendre function - Virchenko, N. A.; Sichkar', Yu, V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We solve and investigate an integral equation with the generalized associated Legendre functionP k m,n (z) by using the fractional integro-differential calculus.